A time of revolution? British local government finance in the 2010s - Neil Amin Smith; David Phillips; Polly Simpson; David Eiser; Michael Trickey (Institute for Fiscal Studies (IFS), 2016)
The local government finance system in England is undergoing genuinely revolutionary change. A highly-centralised system of funding, with central government grants allocated on the basis of councils' relative spending need, is set to be replaced by a system where councils as a group are self-funding and individual councils bear far more spending and revenue risk. The aim of all this is to give councils stronger financial incentives to grow local economies and address underlying spending demand pressures. Accompanying this change will be simplified powers for councils to cut business rates. Decentralisation will be incomplete though - central government plans to keep a tight rein on councils' ability to increase council tax and business rates bills. In Scotland and Wales, little has changed so far, but the next few years could see significant reforms to local tax bases. This is the first report in a new multi-year IFS research programme examining these major changes to local government finance. The programme will consider the impacts of changes so far, provide in-depth analysis of the main issues related to upcoming reforms, and consider the opportunities (and challenges) that would arise from greater fiscal devolution. This report provides an initial look at the changes in councils' spending, funding and funding systems since 2010, and highlights some of the key issues for the planned shift to 100% retention of business rates revenues by councils in England.
Keywords: 330